5z-9=6z

Simple and best practice solution for 5z-9=6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-9=6z equation:


Simplifying
5z + -9 = 6z

Reorder the terms:
-9 + 5z = 6z

Solving
-9 + 5z = 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-9 + 5z + -6z = 6z + -6z

Combine like terms: 5z + -6z = -1z
-9 + -1z = 6z + -6z

Combine like terms: 6z + -6z = 0
-9 + -1z = 0

Add '9' to each side of the equation.
-9 + 9 + -1z = 0 + 9

Combine like terms: -9 + 9 = 0
0 + -1z = 0 + 9
-1z = 0 + 9

Combine like terms: 0 + 9 = 9
-1z = 9

Divide each side by '-1'.
z = -9

Simplifying
z = -9

See similar equations:

| 5/6(-3/10) | | 1000(1+r)*2=1123.60 | | 15x^5-51x^4+18x^3= | | 0.66666666666667x-0.25=-0.25x-3 | | 10-4x=(-18) | | 1-4.5x=2x+7.5 | | -0.25x+4.5=0.66666666666667x-1 | | 7a+6b+2a-3b+2a+3b-5a-4b= | | 2(x)-9=180-x | | 5/18-(-1/3) | | 23-3X=14+2X | | -21b^2+39b+6= | | 2(x)-9=180-y | | -1/7+(-3/7) | | K-12=6 | | -0.5x-3=-0.25x-5 | | 2x^3y+11x^2y+15xy= | | 14+3X=23-2X | | 5x*5=60x*4 | | -x+4=-21 | | 0.9x-1.9=1.5x+2.1 | | 0.5x+3=0.25x+5 | | 0.75x-5=4 | | 5x*5=60 | | x=90-x+22 | | -5+5(x-4)=12x+4-7x | | 28=3m-1d | | 6(1+9c)=-17 | | 2000x/5=50 | | 100x/2=50 | | 32u^2+16uv+2v^2= | | (2*1000*4/2,5)= |

Equations solver categories